An Anatomy of China's Export Boom: An Approach of Trade Margins#. Issue 2 (27th October 2020) - Liu, Hui-Zheng; Li, Shi-Long; Zhang, Kevin H.
Abstract: Using export data with 6-digit HS categories for 1995-2018, we decompose China's export growth into three margins: extensive (EM), price (PM), and quantity (QM). Our estimations suggest that over the 23-year period, QM is a main driving force of China's export boom, accounting for 62% of total contributions, while PM and EM also make significant contributes (26% and 12%, respectively). Dynamic analyses based on four sub-periods suggest informative patterns of export upgrading due to external and internal shocks. In 1995-2001, PM and EM are overwhelming drivers, and QM is even negative. The trade liberalization as China's entering World Trade Organization in 2001 seems to trigger a dominant role of QM in China's explosive export growth in 2001-2013, with slight negative PM in the same two sub-periods. The contribution of EM is negligible in 2001-2008, and negative in 2008-2013 due to falling world demand as a result of the global financial crisis. In more recent years (2013-2018), China's export growth depends more on PM (39% of contributions) and EM (33%), less on QM (28%), suggesting a significant export upgrading.